Trying the stuff of creation: biblicism, tragedy, and romance in the southern fiction of Cormac McCarthy - Thornhill, Christopher John (2017)
This essay presents an analysis of the religious and philosophical ideas present in the early fiction of the contemporary American writer, Cormac McCarthy. It is intended as an intervention into the controversial debate within McCarthy scholarship concerning how the perceptibly ‘religious’ nature of the author’s fictions may be described according to recognised and coherent confessions or perspectives. I argue that McCarthy’s fictions cannot be shown to conform to any particular theological or metaphysical system without significant remainder on account of their being essentially heterogeneous in their construction; and that their religious ‘significance’ lies not in their communication of a positive message, but in the presentation of what is at stake in the contrary interpretations that they uphold. I argue that the essential heterogeneity of McCarthy’s fiction is a development of the author’s reception of the complex aesthetic of Herman Melville’s Moby-Dick and the posture of serious and searching scepticism which that touchstone of American literature presents. The peculiar aesthetic of Moby-Dick alloys the Hellenic and Hebraic imagination, creating a synthesis of the concrete images of mythical and biblical literature, and of the narrative patterns that are native to tragedy and to romance. The effect of this complex is a literary mode that performs a suspension or opposition between a shapeless, circular, mythical world, and the created and teleological worldview declared by the biblical religions. I demonstrate how McCarthy takes up and imaginatively revises this complex of ideas in three novels (Outer Dark, Child of God, and Blood Meridian) in terms of their relation to the motifs and tropes of tragedy and romance, with a particular concern for their relation to the literature of katabasis, or spiritual and metaphysical ‘descent’.